2021
DOI: 10.1002/iub.2445
|View full text |Cite
|
Sign up to set email alerts
|

Tea bioactive components prevent carcinogenesis via anti‐pathogen, anti‐inflammation, and cell survival pathways

Abstract: Cancer seriously impairs human health and survival. Many perturbations, such as increased oxidative stress, pathogen infection, and inflammation, promote the accumulation of DNA mutations, and ultimately lead to carcinogenesis. Tea is one of the most highly consumed beverages worldwide and has been linked to improvements in human health. Tea contains many active components, including tea polyphenols, tea polysaccharides, L-theanine, tea pigments, and caffeine among other common components. Several studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…Basically, thymoquinone causes resistance in the biofilm formation in bacterial species because biofilm formation is the important activity of microbes in their virulence strategy. Thymoquinone also causes hindrance in the oxidative activity of microbes thus reducing the number of microbes (Harzallah et al, 2011;Forouzanfar et al, 2014;Khan, 2018;Fan et al, 2021).…”
Section: Antimicrobial Mechanism Of Thymoquinonementioning
confidence: 99%
See 1 more Smart Citation
“…Basically, thymoquinone causes resistance in the biofilm formation in bacterial species because biofilm formation is the important activity of microbes in their virulence strategy. Thymoquinone also causes hindrance in the oxidative activity of microbes thus reducing the number of microbes (Harzallah et al, 2011;Forouzanfar et al, 2014;Khan, 2018;Fan et al, 2021).…”
Section: Antimicrobial Mechanism Of Thymoquinonementioning
confidence: 99%
“…Various studies established that tea and its flavonoids might aid cardiovascular health (Adhav and Deore, 2022). Tea consumption has been linked to oxidation, anti-inflammation, cancer prevention , cardiovascular preventative medicine, and other health advantages (Fan et al, 2021;Ali et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…l -Theanine, a nonprotein amino acid found in tea plants, accounts for more than half of the total free amino acids in tea Furthermore, research has revealed that l -theanine not only enhances the taste and quality of green tea, but it also has a broad range of positive benefits across species and disease types, including anticancer, antioxidant, antistresser, hepatoprotective, antiaging, antimicrobial, anti-inflammatory, and antianxiety activities . Exposure of human Sertoli cells to l -theanine increased cell proliferation and glucose consumption, leading to a sustained pool of Krebs cycle intermediates …”
Section: Introductionmentioning
confidence: 99%
“…For example, Fu brick tea has a higher content of catechin and flavonoid glycosides, while Pu’er tea has a higher content of catechin derivatives, flavonoids, and alkaloids [ 7 ]. Studies have confirmed that dark tea has a high potential for anti-cancer activity for human health [ 8 , 9 , 10 , 11 ], and it is recommended as a nutritional supplement for the prevention and management of cancer [ 12 , 13 , 14 ]. Therefore, this review summarized the possible anti-cancer mechanisms of dark tea in the past 10 years through articles on the Web of Science, PubMed, and Google Scholar.…”
Section: Introductionmentioning
confidence: 99%